2014
DOI: 10.1155/2014/715845
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Heavy Metals in Dried and Fluid Milk in Peshawar by Atomic Absorption Spectrophotometry

Abstract: Various essential and toxic heavy metals (Ca, Mg, Cu, Zn, Fe, Mn, Pb, Cd, Cr, and Ni) contents in various types of dried (infant formula and powdered) and fluid (fresh and processed) cow milk were assessed by atomic absorption spectrophotometry. The milk samples were collected from local markets of different parts of Peshawar city, Pakistan. Heavy metal concentrations varied significantly depending upon the type of milk. The heavy metal concentrations in most of the samples were within normal and permissible r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 20 publications
4
22
0
Order By: Relevance
“…Pilarczyk et al reported lower values of Cu in cow like our study except buffalo [18]. Lutfullah et al reported lower levels of Cu except buffalo, which are in accordance with present study [19]. …”
Section: Copper Concentrationsupporting
confidence: 92%
See 1 more Smart Citation
“…Pilarczyk et al reported lower values of Cu in cow like our study except buffalo [18]. Lutfullah et al reported lower levels of Cu except buffalo, which are in accordance with present study [19]. …”
Section: Copper Concentrationsupporting
confidence: 92%
“…Meshref et al reported upper limits of Zn in milk and milk products as compared to this study [16]. Lutfullah et al reported greater level of Zn in milk while this study we observed higher value of Zn in camel milk [19].…”
Section: Zinc Concentrationsupporting
confidence: 43%
“…In our study the highest content range was observed especially for Mn, where the difference was even 3.5-times and 6-times in FM and HM milk group, respectively. Similarly, high significant differences in mean values of Mn between products were also described by Lutfullah et al [ 38 ] in formulas available in Pakistan and in mentioned above Jurowski et al [ 36 ] and Ljung et al [ 5 ] works.…”
Section: Discussionsupporting
confidence: 57%
“…Higher than the established in our study Pb content in modified milk was found in other authors [ 52 , 58 ]. In many cases estimated daily Pb exposure was within the safety limits [ 13 , 32 , 35 , 38 , 41 , 42 , 53 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, adding vitamins and trace elements to the products is a common practice among manufacturers. Sometimes, these have been added in large quantities to the point that they have been found to be toxic, even though they are essential in smaller, physiological amounts (12). For example, zinc is important for growth and muscle development of an infant and plays an important role in cell division which is massive during infancy; thus it is intentionally added to infant formulas.…”
Section: Introductionmentioning
confidence: 99%